Bilanguaging Love: Latina/o/x Bilingual Students' Subjectivities and Sensitivities in Dual Language Immersion Contexts. Issue 3 (6th August 2020) - Pacheco, Mariana; Hamilton, Colleen
Abstract : Dual language immersion (DLI) education opens possibilities to leverage Latina/o/x bilingual students' borderlands subjectivities and sensitivities. Yet persistent hegemonic discourses and the instantiation of linguistic and ideological borders in schools denigrate these sensibilities. By drawing on the concepts of bilanguaging and bilanguaging love (Mignolo, 2012), in this study the researchers examine the embodied epistemologies and knowledges a group of Latina/o/x students made visible as they participated in elementary two‐way DLI classrooms. Their analysis reveals first that bilingual students were aware of the linguistic, cultural, and racial and ethnic borders that shaped their Mexicana and Latina identities, but in reifying these borders these Latinas also embodied Spanish, English, and bilingualism in ways that their White peers did not. Second, the researchers analyze relationships, ways of being, and knowledges Latina/o/x bilingual students employed as they supported their peers through the challenges and discomfort around being between languages. These findings challenge views of bilingual students as Other, particularly those of Mexican and Latina/o/x backgrounds whose subjectivities are shaped by modern and colonial projects seeking to manage linguistic difference. Drawing on bilanguaging love as an equity‐oriented guiding principle, the authors argue that DLI can counter these oppressive conditions by elevating these students' borderlands epistemologies and knowledges in schools.